Chitosan Cross‐Linked Graphene Oxide Nanocomposite Films with Antimicrobial Activity for Application in Food Industry. Issue 1 (August 2017) - Grande, Carlos David; Mangadlao, Joey; Fan, Jingjing; De Leon, Al; Delgado‐Ospina, Johannes; Rojas, Juan Gabriel; Rodrigues, Debora F.; Advincula, Rigoberto
Abstract : The present study investigates the synthesis of graphene oxide‐chitosan (CS‐GO) nanocomposite films and their potential application in food packaging. Nanocomposite films were synthesized by cross‐linking graphene oxide with chitosan at high temperatures (120°C). The gel content assay showed an increasing in the % Gel of the nanocomposite film with the introduction of GO, from 64% to almost 89%, which could be related to the cross‐linking reaction between GO epoxy groups and chitosan amine and hydroxyl groups. Mechanical strength, thermal stability, infrared analysis and antimicrobial properties were also investigated. The tensile strength at break increased from 22.7 ± 1.2 to 6471.6 ± 1775.5 MPa when 0.1 wt% of GO was added. Thermal studies showed an increasing in the endothermal peak values with the increasing in GO content, which is also related to the increasing in the cross‐linking degree of the films and water interaction. Finally, the nanocomposites films were evaluated for antimicrobial properties, using E. coli K‐12 MG 1655 (Gram‐negative) and B. subtillis 102 (Gram‐positive). CS‐GO 0.6 wt% films presented the best microbial inactivation against E. coli and B. subtillis, with 22.83% and 54.93% inactivation, respectively. On the other hand, chitosan film (CS) control did not show any antimicrobial property. Therefore, cross‐linking of GO with chitosan improved significantly mechanical and antimicrobial properties of the films. These enhancements in the properties of the films made them suitable for application in food packaging.